Talk Radio, the Mainstream Press, and Public Opinion in Hong Kong - Lee, Francis L. F. (Book collections on Project MUSE., 2014)
Phone-in programmes on public and commercial radio channels have been a staple of popular Hong Kong politics since the 1990s. In the absence of a fully democratic system, they have played an influential role in channeling and mediating public opinion. This work examines the phenomenon of talk radio in Hong Kong, using as its analytical framework the idea of re-mediation.